The future of Bush Brothers & Company : developing a shared vision for a complex family enterprise - Lansberg, Ivan, 1954- (SAGE Knowledge. Cases., 2017)
In early 2014, the family leadership of Bush Brothers & Company, a leading player in canned vegetables (its Bush's Best line dominated the canned-beans market), faced questions about the family's vision for the future in light of an imminent leadership transition: third-generation member, longtime board chair, and, until recently, CEO Jim Ethier planned to leave his role as early as 2015. The family was into its sixth generation, with nearly sixty family shareholders spread across four branches. On the business side, the first non-family CEO was overseeing development of a growth strategy, including ongoing ventures into competitive new markets such as Hispanic foods. Its fourth-generation leaders including Drew Everett (vice president of human resources and shareholder relations, and likely board chair successor), Sarah (chair of the family senate), and Tony (chair of the family's private trust company) faced questions about whom to involve in developing a future vision, how to formulate the vision effectively, and what vision would best serve business and family interests. These questions represented underlying strategic dilemmas, such as whether to have a select group of leaders craft the vision or to solicit input from a wider range of shareholders, and how much to allow the business vision to drive the people vision all framed by recent unsuccessful attempts to develop a shared vision. Resolving these dilemmas successfully would help the family frame and advance its established traditions of leadership, governance, and culture within a truly shared vision that boosted unity and long-term commitment. Students working on the case will gain insights into the framework, process, and challenges associated with developing a shared vision for a complex, multigeneration family enterprise.